Distribution and bioaccumulation of current-use herbicides in sediments and biota from Lake St Lucia (South Africa) and adjacent marine environment - Tyohemba, Raymond Lubem (My University, 2021)
Agriculture is one of the leading sources of pollution impacting rivers, lakes and coastal environments worldwide. Chemical herbicides, in particular, are applied in substantial quantities across vast areas of agricultural land to meet growing global food demands. These compounds are generally highly mobile, susceptible to runoff and may impact environments far from their site of application. As a result, the impact of herbicides on aquatic biological communities is of increasing global concern, particularly in regions important for biodiversity conservation. Lake St Lucia is a large, shallow estuarine system located within iSimangaliso Wetland Park, a UNESCO World Heritage Site on the east coast of South Africa. The system is considered the single most important nursery for estuary-associated fish and invertebrates on the south-east coastline of Africa, and the largest protected estuarine environment for hippos, crocodiles, and aquatic birds on the continent. The offshore marine environment is similarly characterised by high levels of biodiversity and hosts South Africa’s only coral reefs. Despite their protected status, these critical estuarine and marine habitats are vulnerable to external pollution pressures. The catchment areas of Lake St Lucia are under intensive commercial and subsistence agriculture and runoff from farmlands enter Lake St Lucia and ultimately the coastal ocean. This study investigated the prevalence and accumulation of several common herbicides currently used in South Africa to evaluate potential impacts on aquatic and marine communities in iSimangaliso Wetland Park. This was assessed by investigating herbicide concentrations in i) river and lake sediments from Lake St Lucia, ii) in tissues from two fish species commonly found at Lake St Lucia, and iii) in several reef coral invertebrates. Herbicide contaminants including triazines (atrazine, hexazinone, simazine and terbuthylazine), anilides/aniline (acetochlor, alachlor, metolachlor, trifluralin), phenoxy-acids (2,4-D and MCPA) and carbamate (EPTC) were detected in the majority of samples analysed. In sediments, total herbicide concentrations ranged between n.d. – 82.4 ng g-1 dw, with acetochlor (3.77 ± 1.3 ng g-1), hexazinone (2.86 ± 1.1 ng g-1) and metolachlor (10.1 ± 8.7 ng g-1) the dominant herbicide residues. The Mkhuze and Mfolozi rivers were identified as important sources of herbicide contamination to Lake St Lucia. A preliminary ecological risk assessment revealed that current herbicide loads could pose a threat to aquatic life, particularly at the algal and aquatic invertebrate community level. Tissue analyses revealed widespread herbicide contamination in fish from Lake St Lucia, with total concentrations in the range of 44.3 – 238 ng g-1 and 72.2 – 291 ng g-1 dw for Clarias gariepinus (African sharptooth catfish) and Oreochromis mossambicus (Mozambique tilapia), respectively. A preliminary human health risk assessment indicated no dietary risk associated with the consumption of both fish species, but that exposure to atrazine and simazine bioaccumulation through life-time consumption presented potential cancer risk to local communities. Herbicide residues were detected in >95% of coral tissue samples, with total average concentrations across sampling sites ranging between 25.2 and 51.3 ng g-1 dw. Acetochlor, alachlor and hexazinone were the predominant analytes detected at all sites, but concentrations varied markedly among coral species. On average, highest total herbicide concentrations were measured in soft coral (Sarcophyton glaucum; 90.4 ± 60 ng g-1 and Sinularia gravis; 42.7 ± 25 ng g-1) and sponge (Theonela swinhoei; 39.0 ± 40 ng g-1) species, while significantly lower concentrations characterised the two hard coral species sampled (Echinopora hirsutissima; 10.5 ± 5.9 ng g-1 and Acroporaaustera; 5.20 ± 4.5 ng g-1). Latitudinal variation in herbicide concentrations suggested that runoff originating from St Lucia estuary and Maputo Bay were likely the major sources of contamination to coral reefs. Results from this study provide first insight into the distribution and bioaccumulation of herbicide contaminants in iSimangaliso Wetland Park. Findings indicate that herbicides accumulate readily within aquatic and marine biota, presenting concerns not only for park management in the region, but for biodiversity conservation globally. Chronic exposure of organisms to herbicides remains largely understudied and potential impacts on ecosystem communities cannot at present be evaluated. Impacts may be subtle and include reproductive suppression or reduced resilience to disease and climate change. Urgent toxicological information is required to help inform monitoring programs and management strategies
A thesis submitted to the Faculty of Science, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021